L’action de l’arsene, en tant qu’element polluant sur les poissons d’eau donce - Șerbănescu, Octavian; Mihnea, Radu; Bilal, Icmet; Cuingioglu, Elvira (Cercetări Marine - Recherches Marines, 2026)
Data concerning the influence of the arsenic ions, which may appear in fishing basins from the waste waters of a chemical plant, upon the freshwater fishes are presented in the paper. Experiments were carried out on two races of carp (Cyprinus carpio and Cyprinus carpio galitianus), than on Rutilus rutilus carpathorossicus and on Perea fluviatilis fluviatilis, with trivalent and pentavalent arsenic salts. The authors check the toxicity of each type of ion, taking into account the solubility of the respective salts- The behavior of the fish at various concentrations between 0,5 and 100ppm As was observed.